Promoting Gypsy children's behavioural engagement and school success: Evidence from a four‐wave longitudinal study. (4th May 2017) - Rosário, Pedro; Núñez, José Carlos; Vallejo, Guillermo; Azevedo, Raquel; Pereira, Raquel; Moreira, Tânia; Fuentes, Sonia; Valle, Antonio
Abstract : Low schooling, high non‐attendance and school dropout rates are critical phenomena within disadvantaged groups, especially among the Gypsy community. For example, in the UK, 10%–25% of Gypsy children do not attend school regularly and have significantly higher levels of overall absence from school (percentage of half‐day sessions missed) than pupils from other ethnic groups. In Portugal, available data on Gypsy children is sparse, yet data from one geographic region of the country reports high school failure (45%) and dropout rates (15%) among this population. The present study assessed the efficacy of a four‐year intervention to promote Gypsy children's behavioural engagement and school success. Gypsy communities were contacted and 30 children participating in the four waves were randomly distributed into control and experimental groups. Every school day throughout four years, 16 children in the experimental group were called at home and invited to go to school. The effectiveness of the intervention was evaluated in four waves (at the end of each of the four school years), assessing behavioural engagement (i.e. school non‐attendance, classroom behaviour) and school achievement (i.e. mathematics achievement, student progression). Findings show the efficacy of the intervention on promoting behaviour engagement and academic success without devaluing Gypsy people's culture.